“An Intrinsic Program Determines Key Age-Associated Changes in Adaptive Immunity That Limit Response to Non-Pathogens” - Swain, Susan L.; Kugler-Umana, Olivia; Tonkonogy, Susan L. (Frontiers in Aging, 2021)
With aging the adaptive immune system changes dramatically, leading to weakened response to newly encountered antigens and poor efficacy of vaccines. Our recent studies, in germ-free mice, suggest these changes are largely intrinsic, and driven by homeostasis. A shared pattern emerges in both CD4 T and B cells such that they require higher levels of pathogen recognition to mount a strong response.